Naud-et-al-Data - Naud, Lucy; Måsviken, Johannes; Freire, Susana; Angerbjörn, Anders; Dalen, Love; Dalerum, Fredrik (Dryad Digital Repository, 2019)
Raw data for Naud et al. Ecology and evolution. File includes a data table containing % vegetation cover, plant species richness, plant Shannon evenness, and three distances to centroids (which have been used as measurements of beta diversity on three different spatial scales), as well as a binary presence - absence matrix used for community structure calculations.